Children deny that God could change morality - Reinecke, M; Solomon, LH (Elsevier, 2023)
Can moral rules change? We tested 129 children from the United States to investigate their beliefs about whether God could change widely shared moral propositions (e.g., “it's not okay to call someone a mean name”), controversial moral propositions (e.g., “it's not okay to tell a small lie to help someone feel happy”), and physical propositions (e.g., “fire is hotter than snow”). We observed an emerging tendency to report that God's ability to change morality is limited, suggesting that children across development find some widely shared aspects of morality to be impossible to change. Some beliefs did shift over development, however: 4- to 6-year-olds did not distinguish among God's ability to change widely shared moral, controversial moral, and physical propositions, whereas 7- to 9-year-olds became increasingly confident that God could change physical and controversial moral propositions. Critically, however, younger children and older children alike reported that widely shared aspects of morality could not be altered. According to participants, not even God could change fundamental moral principles.